PENGARUH AMALIAH TQN TERHADAP SIKAP BELAJAR PESERTA DIDIK DI MASA PANDEMI COVID-19 - Nisa, Zahro Khoerun; Bassar, Agus Samsul (THORIQOTUNA: Jurnal Pendidikan Islam, 2021)
The study aims to determine the effect of TQN's practice on students' learning attitudes during the Covid-19 pandemic. The research method that the author uses is a descriptive method with a quantitative approach. The population is all students of MA Serba Bakti Suryalaya Tasikmalaya that is 354 people. While the sample is 32 respondents of class XII Religion 1. The sampling technique used is purposive sampling. While the data collection techniques used were observation, questionnaires, and interviews. The data analysis technique for each variable uses the calculated average while the correlation analysis of the two variables uses the Spearman rank correlation (rs). The correlation analysis of the influence of amaliah TQN on students' learning attitudes during the Covid-19 pandemic at MA Serba Bakti Suryalaya Tasikmalaya was in high clarification.) The results of hypothesis testing obtained t count of 4.5605 and t table of 1.697. Thus, t count 4.5605 > t table 1.697. This means that the alternative hypothesis (Ha) which states that there is a significant effect between Suryalaya's TQN practice and students' learning attitudes during the Covid-19 pandemic at MA Serba Bakti Suryalaya Tasikmalaya is accepted and (Ho) is rejected.